Study on pig cough recognition and spatial localization based on multi-source noise separation - Yue Cao; Zhe Yin; Yongpeng Duan; Penghui Li; Jing Zeng; Linwei Li; Guangying Hu; Zhenyu Liu (Computers and Electronics in Agriculture, 2026)

Integrative genomic analyses reveal genetic structuring and cyto-nuclear incongruences within the Corbicula species complex in China - Yangxin Tang; Linwei Liu; Jie Pi; Xinhua Liu; Jianguo Xiang; Joong-Ki Park; Neil E. Coughlan; Deliang Li (Molecular Phylogenetics and Evolution, 2026)

Oral administration of dopamine boosts anti-Vibrio immunity in shrimp through Dorsal pathway activation - Zi-ang Wang; Shun Liu; Zexu Zhao; Xiaojia Liao; Linwei Yang; Hongliang Zuo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2026)

Citrate-mediated differential modulation of cytotoxicity induced by nano-zero-valent iron and ferrous ions in human lung epithelial cells (A549) - Linwei Liu; Chi Zhang; Rui Zheng; Yuwei Pan; Lu Yang; Shilin Shi; Limin Cao; Ying Zhang (Process Safety and Environmental Protection, 2026)

Cosmic spike removal based on multi-feature fusion for long-time integrated Raman spectral detection - Huijie Wang; Xu Liu; Xujin Hu; Wenhui Sun; Shuang Xiong; Jinjin Wu; Linwei Shang; Jianhua Yin (Analytica Chimica Acta, 2026)

Salicylic acid-mediated biosynthesis of anti-oomycete diterpenoids in Euphorbia lathyris L. suspension cells - Pirui Li; Xi Sun; Guodong Zhang; Bi Wang; Chenxing Xiao; Mei Tian; Shu Xu; Hui Liu; Xu Feng; Linwei Li; Wanli Zhao; Yu Chen (Plant Cell Reports, 2026)

Optimization of the initial performance of solid oxide fuel cells base on reduction and operating temperature - Peiyuan Liu; Xiaoyu Wang; Linwei Ma; Minfang Han (Chemical Engineering Journal, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Isolation and characterization of a novel reassortant H3N8 avian influenza virus from chickens in Eastern China - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Taoming Tang; Zhigang Wu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2026)

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Acicular berthierine-chamosite in coal and lung cancer tissues of Xuan Wei, China - Zheshen Han; Hongli Lin; Renyue Ji; Lijun Liu; Pei Zhang; Chao Jiang; Shijie Zhu; Jialin Xu; Zhenghong Yang; Yunchao Huang; Toshihiro Kogure; Fang Guo; et al. (Journal of Hazardous Materials, 2026)

Stress Behaviors of Cartilage with Defect and After Repair in Total Knee Under Compression Loading - Xianglong Lin; Shilei Wang; Bolun Liu; Lilan Gao; Linwei Lyu; Chunqiu Zhang (Journal of Medical and Biological Engineering, 2025)

Amino acid substitutions associated with adaptation of novel H10N3 and H10N5 avian influenza viruses to mice - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Archives of Virology, 2025)

Formaldehyde emissions in tanker truck cabins: Observation, deep learning prediction and health risk assessment - Rui Zhang; Dongdong Guo; Ruixiu Jiang; Honglin Cao; Yunjia Wu; Lirong Kou; Meng Wang; Linwei Xi; Yang Liu; Haimei Wang; Jianyin Xiong (Science of The Total Environment, 2025)

The influences of China's Cultivated Land Fertility Protection Subsidy policy on farmers' agro-eco-environmental protection behavior: an application of the extended theory of planned behavior - Ting Liu; Linwei Du; Jiaona Hou; Xiancheng Zeng; Wenyan Zhang; He Xu (Journal of Environmental Management, 2025)

Biobased carbon quantum dots: An emerging nano-enabled paradigm for pesticide removal and sustainable plant protection - Usman Arshad; Dan Chen; Haichao Cao; Chao Feng; Linwei Liu; Muhammad Amjad Ali; Zhang Wanhong; Yishan Li; Lijun Jiang; Jinguang Yang (Science of The Total Environment, 2025)

A novel LRR domain-containing C-type lectin gene with immune regulatory functions protects Penaeus vannamei against Vibrio parahaemolyticus infection - Kejia Weng; Ruoyu Liu; Chengqi Xiong; Yuxin Shi; Wenqian Chen; Chuanqi Wang; Linwei Yang (Fish & Shellfish Immunology, 2025)

Identification of the exposure pathway to micro-scaled biogenic silica debris via diet and its potential effect in promoting esophageal squamous cell carcinoma - Shenxi Deng; Yi Yang; Erica Celeste Conway; Si Li; Cha Huang; Zigu Chen; Haisheng Wu; Yuan He; Shuzhe Xie; Aifang Ji; Jingyan Zhang; Yansheng Gu; et al. (Journal of Hazardous Materials, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Spermatogenesis and ultrastructure of the spermatozoa at three ploidy levels in the bivalve species, Corbicula fluminea - Jie Pi; Yangxin Tang; Ying Fu; Xu Wang; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Tissue and Cell, 2025)

Genetic assessment of feed efficiency in the spotted Babylon Babylonia areolata - Linwei Nie; Yijie Kong; Ziyi Ma; Jingqiang Fu; Shengtai Liu; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2025)

Combined multispectral analysis and molecular docking to research the interaction of soybean isolate protein with different kinds of phospholipid liposomes and its effect on liposome properties - Linwei Zhao; Chunlei Liu; Tong Wang; Libin Sun; Fei Wu; Dianyu Yu (Food Chemistry, 2025)

DRAM2 inhibits white spot syndrome virus infection via activating autophagy in Penaeus vannamei - Xiyu Huang; Mingming Zhao; Jieyu Huang; Mingjian Liu; Linwei Yang; Chuanqi Wang (Fish & Shellfish Immunology, 2025)

Genetic advancements and future directions in ruminant livestock breeding: from reference genomes to multiomics innovations - Songsong Xu; Zhanerke Akhatayeva; Jiaxin Liu; Xueyan Feng; Yi Yu; Bouabid Badaoui; Ali Esmailizadeh; Juha Kantanen; Marcel Amills; Johannes A. Lenstra; Anna M. Johansson; David W. Coltman; et al. (Science China Life Sciences, 2025)

Temperature drives reproductive activity in a rare trioecy population of Corbicula clams - Jie Pi; Yangxin Tang; Neil E. Coughlan; Linwei Liu; Xu Wang; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

Impact of water temperature experienced in early life of Dosidicus gigas on its adult growth - Yating Dan; Bilin Liu; Leilei Zou; Jie Lu; Linwei Song (Fisheries Research, 2025)

Baseline sensitivity and resistance risk of Sclerotinia sclerotiorum to glabridin and the possible anti-fungal mechanism - Shu Xu; Chenyang Liu; Jin Chen; Linwei Li; Siwei Qiao; Mei Tian; Qian Zhou; Xingzeng Zhao; Yu Chen; Fei Liu; Xu Feng (Pesticide Biochemistry and Physiology, 2024)

Preparation of high-affinity and high-specificity monoclonal antibody and development of ultra-sensitive immunoassay for the detection of 1-aminohydantoin, the metabolite of nitrofurantoin - Hongfei Yang; Liangni Qin; Hao Wen; Mingyue Ding; Linwei Zhang; Jiaxu Xiao; Jixiang Liang; Yiting Liu; Ziyan Yu; Dapeng Peng (Food Chemistry, 2024)

Extraction and purification, pharmacological action, synthesis and product development of salidroside: a review - Yaxiao Liu; Linwei Dan; Jiamei Tang; Zitong Yin; Longzhu Yang; Dongdong Zhang; Xiaomei Song; Wei Wang; Yuze Li (Medicinal Chemistry Research, 2024)

Niche similarity accompanying COI genetic differentiations in asexual and sexual Corbicula lineages within East and Southeast Asia - Yangxin Tang; Jie Pi; Neil E. Coughlan; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2024)

Targeted discovery of unusual diterpenoids with anti-fungal activity from the root of Euphorbia lathyris - Yiwei Wang; Shu Xu; Guodong Zhang; Pirui Li; Chenyang Liu; Jiarui Zhou; Xu Feng; Linwei Li; Yu Chen (Phytochemistry, 2024)

Advancements in production, assessment, and food applications of salty and saltiness-enhancing peptides: A review - Yingying Hu; Iftikhar Hussain Badar; Yue Liu; Yuan Zhu; Linwei Yang; Baohua Kong; Baocai Xu (Food Chemistry, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

In vivo study of chelating agent-modified nano zero-valent iron: Biodistribution and toxicity in mice - Minhui Hou; Linwei Liu; Yuqing Zhang; Yuwei Pan; Ning Ding; Ying Zhang (Water Research, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Research on the Penetration Coefficient During the Rock Drilling Process by Cyclic Impact - Jinguang Li; Yu Liu; Linwei Wang; Yumeng Sun; Xin Li; Junjie Wang (Rock Mechanics and Rock Engineering, 2024)

Orange-spotted grouper IFNh response to NNV or MSRV and its potential antiviral activities - Siyou Huang; Rui Zheng; Yiling Kang; Linwei Yang; Jie Gao; Qingqing Liu; Shaoping Weng; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Characterization of aquifer heterogeneity by tomographic slug test responses considering wellbore effects - Quan Liu; Linwei Hu; Rui Hu; Ralf Brauchler; Yixuan Xing; Junjie Qi; Thomas Ptak (Journal of Hydrology, 2023)

A large-scale climate-aware satellite image dataset for domain adaptive land-cover semantic segmentation - Songlin Liu; Linwei Chen; Li Zhang; Jun Hu; Ying Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

A supply chain allocation method for environmental responsibility based on fossil energy as the anchor for carbon responsibility - Chin Hao Chong; Yuan Gao; Linwei Ma; Zheng Li; Weidou Ni; Xiaoyong Zhou; Silvio Cristiano; Fanxin Meng; Wen Zhang; Ningyu Yan; Yan Hao; Gengyuan Liu (Journal of Cleaner Production, 2023)

Thallium release from biochar-amended soil to runoff in laboratory experiments - Lezhang Wei; Dafeng Cai; Fangqing Li; Yu Liu; Linwei Zeng; Dinggui Luo; Xuexia Huang; Tangfu Xiao; Hang Shi; Haiqi Yan (Environmental Pollution, 2023)

Clinical Features and Skin Microbiome of Tinea Scrotum: An Observational Study of 113 Cases in China - Zixiang Si; Juan Bai; Linwei Wei; Honglei Zhao; Songting Wang; Bin Liu; Jingjing Xu; Hong Fang; Zongxin Ling; Jianjun Qiao (Mycopathologia, 2023)

Fluoxetine alleviates postoperative cognitive dysfunction by attenuating TLR4/MyD88/NF-κB signaling pathway activation in aged mice - Yusheng Yao; Daoyi Lin; Yuzhi Chen; Linwei Liu; Yushang Wu; Xiaochun Zheng (Inflammation Research, 2023)

Slope Instability Analysis of the Qiongdongnan Basin in the Northern Part of the South China Sea: Implications for the Risk Evaluation of Deepwater Drilling - Linwei Ma; Shiguo Wu; Yanrui Liu; Jin Sun; Min Ouyang; Qingping Li; Yongpeng Qin; Dawei Wang (Journal of Ocean University of China, 2023)

Structural control on the Baiyinha'er gold mineralization (Southern Central Asian Orogenic belt) related to Early Paleozoic Paleo-Asian Oceanic subduction - Junlai Liu; Tao Jin; Yangwang Ou; Linwei Li; Cheng Zhang; Tianjiao Lu; Xiaoyu Chen (International Journal of Earth Sciences, 2022)

A comparison of next-generation sequencing with clone sequencing in the diet analysis of Asian great bustard - Minghao Gong; Yu Ning; Morigen Han; Chenyang Zhao; Jingxing Tian; Linwei Li; Hongye Xiao; Gang Liu (Conservation Genetics Resources, 2019)

Expanding indole diversity: direct 1-step synthesis of 1,2-fused indoles and spiroindolines from 2-halo anilines for fast SAR antiviral elucidation against tobacco mosaic virus (TMV) - Linwei Chen; Yongxian Liu; Hongjian Song; Yuxiu Liu; Lizhong Wang; Qingmin Wang (Molecular Diversity, 2017)

Reconstructing changes in Atlantic thermohaline circulation during the 20th century under two possible scenarios - Jun Cheng; PinWen Guo; FuYing Zhang; ZhengYu Liu; LinWei Liu; WenXian Qiu (Science China Earth Sciences, 2013)